Pengaruh Model Missouri Mathematics Project (MMP) terhadap Hasil Belajar Matematika ditinjau dari Kemandirian Belajar - Indrawati; Zaida, Sismy; Lestari, Putu Eka Pethiwi (Circle: Jurnal Pendidikan Matematika, 2024)
The aim of this research is to determine the interaction between learning models and learning independence on students' mathematics learning outcomes. The type of research used is quasi experimental research, and the research design used is a 2x3 factorial design. Research data was obtained from test results and student learning independence questionnaires. Test the research hypothesis using two-way analysis of variance with unequal cells. Research results: 1) Learning outcomes with the application of the MMP model are better than conventional models; 2) Students who have high learning independence have better learning outcomes compared to students who have medium and low levels of learning independence, likewise students with moderate learning independence have better learning outcomes compared to students who have low levels of learning independence; 3) Students with high, medium or low learning independence in the MMP learning model have better learning outcomes compared to the learning outcomes of students who have independence in the same category in the conventional model. Thus, it can be concluded that the MMP model of learning obtains better learning outcomes compared to learning with the conventional model. Apart from that, student learning independence greatly influences the learning outcomes obtained. Thus, students' mathematics learning outcomes are equally influenced by the learning model and student learning independence.